Cryptosporidiosis diagnosed using metagenomic next-generation sequencing in a healthy child admitted to pediatric intensive care unit: a case report - Liu, Xiaoyi; Wang, Jing; Liu, Jun; Li, Xuming; Guan, Yuanlin; Qian, Suyun; Jia, Xinlei (Frontiers in Cellular and Infection Microbiology, 2023)
Cryptosporidium infections in humans typically result in symptoms such as abdominal pain and diarrhea. When the diarrhea is severe, it can cause serious complications and even be life-threatening, especially in patients with compromised immune systems.Here, we reported the use of metagenomic next-generation sequencing (mNGS) to assist in the diagnosis and treatment of a 10-year-old boy with severe Cryptosporidium infection. Despite the absence of any history of immunocompromise, the infection still resulted in severe symptoms, including shock, as well as damage to his pancreas and kidneys. The mNGS tests detected the presence of Cryptosporidium parvum when conventional methods failed. The patient received anti-parasite treatment along with supportive care to manage the condition. With disease surveillance based on regular clinical tests and sequential mNGS tests, the child recovered from the severe conditions.Our study emphasized the importance of recognizing the potential severity of Cryptosporidium infection, even among individuals with normal immune systems. Timely diagnosis and ongoing monitoring are essential for patient prognosis.